Shallow-water stenopodidean and caridean shrimps from Abrolhos Archipelago, Brazil: new records and updated checklist - Soledade, Guidomar O.; Fonseca, Mytalle S.; Almeida, Alexandre O. (Zootaxa, 2015)
This study deals with a recent collection of stenopodidean and caridean shrimps made in the Abrolhos Archipelago, Bahia, Brazil, in July and August 2013. Sampling was carried out in the vicinity of Ilha de Santa Bárbara (17°57’49”S 38°41’53”W). Specimens were obtained by hand or using small hand nets in tide pools or under rocks in the intertidal zone. Part of the material was collected by scuba diving in the shallow subtidal, to a maximum depth of 11 m. We obtained a total of 18 species, 12 of which are reported for the first time for the Abrolhos and 4 as new records for the state of Bahia. The distributions of Microprosthema semilaeve (von Martens, 1872), Typton gnathophylloides Holthuis, 1951, Alpheus verrilli (Schmitt, 1924) and Alpheopsis cf. trigona (Rathbun, 1901) are extended from their previously known ranges. The occurrence of Automate cf. rectifrons Chace, 1972 on the Brazilian coast is confirmed. We thus provide an updated checklist of stenopodidean (2 species) and caridean (29 species) shrimps from the Abrolhos Archipelago, incorporating and critically evaluating previous records.